The Influence of Brand Image, Service Quality, Customer Expectation and e-WOM on Customer Satisfaction and Customer Loyalty in International Chain Hotel at Batam City - Erilia Kesumahati; Mega Augustina Ng; Wisnu Yuwono (Jurnal Manajemen Stratejik dan Simulasi Bisnis, 2025)
The high competition in the hospitality industry drives companies to improve customer satisfaction and customer loyalty through appropriate marketing and service strategies. The aim of this study is to examine how customer satisfaction and loyalty are affected by brand image, service quality, customer expectation, and electronic Word of Mouth (e-WOM) on international chain hotel. This study uses a quantitative method with a Structural Equation Modeling (SEM) approach based on Partial Least Square (PLS-SEM), processed using SmartPLS 3.0 and SPSS 26. The sample in this study consisted of 495 respondents selected purposively, with the criterion of having visited an international hotel in the last two years. The analysis results show that brand image does not have a significant effect on customer satisfaction and customer loyalty. Service quality has a significant positive effect on both. Customer expectation does not affect customer satisfaction but has a significant effect on customer loyalty. E-WOM has a significant effect on customer satisfaction but not on customer loyalty. Meanwhile, customer satisfaction proves to be the most significant factor in influencing customer loyalty. These findings have important implications for hotel management in designing strategies to improve service quality and customer experience as an effort to build long-term loyalty.